Credit default swaps, bond spreads and the bond market - Zhu, Meicheng (2014)
With the rapid development of the credit default swap (CDS) market, the issue of how the introduction of CDSs affects the corporate bond market has been of particular interest to researchers and policy makers. This has been investigated in the literature from two perspectives. One is to examine the relationship between the CDS and the bond markets in price discovery, and the other is concerned with researching the CDS trading effects on bond spreads. Referring to the former approach, most relevant studies find a dominant role of the CDS market over the bond market in the price discovery process, based on an analysis of CDS prices and credit spread data (e.g. Blanco et al., 2005; Baba and Inada, 2009). The latter is considered a more direct approach which aims to examine whether and how the corporate bond market and bond spreads are influenced by the onset of CDS trading. A limited number of leading articles in the literature following the second approach include Ashcraft and Santos (2009), Massa and Zhang (2012), and Shim and Zhu (2014).